The Number of Chains of Subgroups in the Lattice of Subgroups of the Dicyclic Group - Ju-Mok Oh; Yunjae Kim; Kyung-Won Hwang (Discrete Dynamics in Nature and Society)
We give an explicit formula for the number of chains of subgroups in the lattice of subgroups of the dicyclic group B4n of order 4n by finding its generating function of multivariables.